DEVELOPMENT OF MODERN THOUGHTS IN ISLAM - Eka Hendry Ar; Reviewed by: Suhardiman (Al-Albab, 2013)
For more than 14 centuries, history has proved that Islamic teachings come with a variety of thoughts, social cultural backgrounds, periods through which the development and the dynamics evolved. The primary mission of mankind as the khalifah fil ardh (the caliph of the earth, is to practice the Islamic teachings (Shariah) in accordance with the provisions of the primary source of Islam itself, i.e. the Qur’an and Hadith. At least, a long history of Islam as a religion of revelation suggests that the existence of Islamic teachings can grow and develop in every corner of the world, with a variety of spreading patterns that give the nuances and the mosaics in the development of the religion the present day.